(untitled) (Research, Society and Development, 2021)
School alimentation, better known as “school meals” are a right of students in public schools. The purpose of this food is to contribute to the integral development of students and consequently collaborate with their learning. The resources destined for school meals are transferred monthly, based on the per capita amount, it is in the school census, so the state and federal governments are responsible for the transfer of funds to public schools. With the receipt of funds, it is determined that schools report annually on the amounts used. In the current market there are little software that help with accountability related to meals, besides not being free. Therefore, this study aims to describe the activities inherent to the analysis and modeling of software on the Web platform in order to manage the resources destined for school meals. Methodologically, the study is classified as being of a qualitative nature, used through interviews and bibliographic research. With the development of the software, it is expected to contribute to the improvement of the control of data related to school meals, aiming to improve the use of resources destined through the computerized planning of menus and the generation of reports.